A Retrospective Analysis for Patients with HER2-Positive Gastric Cancer Who Were Treated with Trastuzumab-Based Chemotherapy: In the Perspectives of Ethnicity and Histology - Yi, Jun Ho; Kang, Jung Hun; Hwang, In Gyu; Ahn, Hee Kyung; Baek, Hyun Jin; Lee, Soon Il; Lim, Do Hyoung; Won, Young-Woong; Ji, Jun Ho; Kim, Hyo Song; Rha, Sun Young; Oh, Sung Yong; et al. (Cancer research and treatment, 2016)
While the Trastuzumab for Gastric Cancer (ToGA) trial demonstrated the efficacy and safety of trastuzumab-based chemotherapy in HER2-positive metastatic gastric cancer, the overall survival (OS) benefit was not found in Asian and diffuse-type cancer patients. The aim of the study is to investigate predictive markers for trastuzumab-based chemotherapy. Data of patients with HER2-positive gastric cancer treated with trastuzumab-based chemotherapy were analyzed retrospectively. A total of 168 Asian patients were included. The median age was 60 years (range, 27 to 85 years) and the male:female ratio was 118 (70.2%):50 (29.8%). Fourteen (8.3%), 63 (37.5%), 75 (44.6%), and 11 (6.5%) patients had well, moderately, poorly-differentiated tubular adenocarcinoma and signet ring cell carcinoma, respectively. With 14 complete responses and 73 partial responses, the response rate was 50.6%. The median progression-free survival (PFS) was 10.2 months (95% confidence interval [CI], 8.7 to 11.7), and the median OS was 18.5 months (95% CI, 16.4 to 50.6). Next, we investigated the effect of poorly-differentiated histology (PDH, poorly-differentiated tubular adenocarcinoma+signet ring cell carcinoma) on clinical outcomes. The median PFS (8.9 months vs. 11.5 months, p=0.16) was slightly inferior in PDH patients, and the median OS was significantly shorter in PDH patients (14.6 months vs. 19.0 months, p=0.025). While subset analysis of the ToGA trial demonstrated that trastuzumab-based chemotherapy may not be beneficial for Asians and patients with PDH, our data may suggest that even in Asian patients and patients with PDH, trastuzumab-based chemotherapy could be associated with improved clinical outcomes in patients with HER2-positive gastric cancer.